AIDS in België - SIDA en Belgique. (Brussel : Instituut voor Hygiëne en Epidemiologie, 1986)
Fonds Suzan Daniel (FSD)
Periodiciteit : driemaandelijks
Redactie : Juliette Wytmanstraat 14, 1050 Brussel
Nederlands
Periodiek